Non-Monetary Incentives to Improve Job Performance: A Study at Property Company in Penang - Abu Bakar, Nur Fatin Nazierah; Mustafa Kamil, Bidayatul Akmal; Abd Hamid, Siti Norasyikin; Abd Rani, Shamsul Huda (2017)
The purpose of this study is to examine the relationship of non-monetary incentives such as flexible working schedules, recognition and career development on job performance.The respondents of the study were among employees who work with a property company in Penang.The objectives of this research are (i) to determine the relationship between flexible working schedules and job performance, (ii) to identify the relationship between recognition and job performance, (iii) to examine the relationship between career development and job performance and (iv) to determine the factors influence flexible working schedules, recognition and career development towards job performance.In this study, the quantitative method was implemented. In assessing the relationship between the variables, a total of 91 questionnaires were analysed using descriptive and inferential data analysis technique. The method of analysis used in this study includes reliability test, Pearson correlation and multiple regression.The findings of this research reveal that flexible working schedules, recognition and career development has significant relationship on employees’ job performance.The result of this research may assist the organization plan to increase the employees’ job performance.